Nutritional status of female rats after acute intoxication with ethyl alcohol and treatment with ketoprofen lysine salt or ketoprofen - Nieradko-Iwanicka, Barbara; Ruszel, Kinga (Current Issues in Pharmacy and Medical Sciences, 2024)
Ketoprofen lysine salt (KL) is a new non- steroidal anti-inflammatory drug (NSAID) competing with ketoprofen (K) on the market. The former is believed to have gastroprotective properties and both to kill acute pain. In East Europe binge drinking and taking NSAIDs after is common. Some people use NSAIDs to treat the discomfort when they sober up. Vomiting after alcohol intoxication and gastritis after use of NSAIDs may produce malnutrition. The aim of the study was to compare nutritional status in female rats treated with KL or K after acute intoxication with ethyl alcohol. In this animal model we wanted to mimic human cases of NSAIDs use on the day(s) after binge drinking. The experiment was carried out on 36 female Wistar rats divided into 6 groups of 6: 1. treated with 50% etanol; 2. 0.9% NaCl; 3. 0.9% NaCl and K; 4. 50% etanol and K; 5. 0.9% NaCl and KL; 6. 50% etanol and KL.On day 7 animals were sacrificed. Their body, liver and kidney mass was recorded. The blood was obtained to measure blood morphology and biochemical parameters. K and alcohol in group 4 limited body mass gain (p